2013
DOI: 10.1182/blood-2013-08-520890
|View full text |Cite
|
Sign up to set email alerts
|

Smoldering multiple myeloma requiring treatment: time for a new definition?

Abstract: Smoldering multiple myeloma (SMM) bridges the gap between monoclonal gammopathy of undetermined significance (a mostly premalignant disorder) and active multiple myeloma (MM). Until recently, no interventional study in patients with SMM showed improved overall survival (OS) with therapy as compared with observation. A report from the PETHEMA-GEM (Programa Español de Tratamientos en Hematologica) group described both fewer myeloma-related events and better OS among patients with high-risk SMM who were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 78 publications
4
71
0
2
Order By: Relevance
“…To date, high-risk SMM patients do not receive treatment until they progress to overt MM and experience end-organ damage (Supplemental Figure 6). This is because, although a number of useful prognostic factors have been identified, there is a lack of accurate and sensitive biomarkers that can preemptively identify high-risk SMM (26). Being able to identify patients with high-risk SMM will provide an opportunity for changing the treatment paradigm to develop effective preventive and early treatment strategies for MM.…”
Section: Discussionmentioning
confidence: 99%
“…To date, high-risk SMM patients do not receive treatment until they progress to overt MM and experience end-organ damage (Supplemental Figure 6). This is because, although a number of useful prognostic factors have been identified, there is a lack of accurate and sensitive biomarkers that can preemptively identify high-risk SMM (26). Being able to identify patients with high-risk SMM will provide an opportunity for changing the treatment paradigm to develop effective preventive and early treatment strategies for MM.…”
Section: Discussionmentioning
confidence: 99%
“…A study recently demonstrated that high-risk SMM seemed to highly benefit from early treatment approach in terms of prolonged TTMM and more importantly OS, rather than to wait for development of symptomatic MM to start treatment (20). The definition of early MM remains debatable, and whether all currently defined high-risk SMMs are early MM, remains however an important matter of debate (21). Similarly, an early treatment for SP should only be proposed to patients identified as being at higher risk, through well-defined prognostic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Recent data showed that a subset of patients who lacked organ damage and were classifi ed as SMM according to the previous IMWG criteria have active disease that may benefi t from treatment. (4,5) The IMWG has updated its defi nition of MM to take these changes into account. (6) The following are the key changes made in the 2014 IMWG consensus on diagnosis of MM:…”
Section: Diagnosis Staging and Risk Stratification Backgroundmentioning
confidence: 99%